Photothermal performance of nanofluids: An experimental study on direct absorption solar energy conversion using graphene oxide and its binary composites for water purification - Abdul Sattar; Bai Bofeng; M. Adeel Munir; Muhammad Farooq; S. Bilal; M. Imran Khan; Noreen Sher Akbar; Mohammed Ilyas Khan; Mohammad Rehan; Fahid Riaz (Energy Conversion and Management: X)
Water scarcity affects two-thirds of the world’s population and is one of the most important challenges to human development. Nanotechnology led by solar evaporation is emerging to solve water resource problems by absorbing solar energy to vaporize nanofluid samples, especially in areas where seawater resources are abundant and economical. For this purpose a direct absorption solar collector set-up was constructed to measure evaporation rate under natural solar light, a pyranometer to measure light intensity, a K-thermocouple system to measure temperature and digital balance to measure mass loss. Then, nanofluids were prepared using a standard two-step method, and characterized using scanning electron microscopy and ultraviolet–visible spectroscopy. Photothermal experiments were carried out by weight concentrations (0.02 % and 0.03 %) for ∼ 5h each sunny day. The photothermal performance and specific absorption rate (SAR) of graphene oxide–zinc oxide (GO–ZnO) and graphene oxide–iron oxide (GO–FeO) nanofluids at different mixing ratios were investigated. The contribution of sensible heat based efficiency and evaporative based efficiency was revealed in context of photothermal efficiency. An increase in photothermal efficiency and a decrease in specific absorption rate (SAR) were observed with increasing nanoparticle concentration. 92 % photothermal conversion efficiency in the case of pure (100 %) GO at 0.03 wt% was obtained which is the highest among all the nanofluids used in this work. The best photothermal performance of pure (100 %) GO was achieved due to maximum solar absorption, dark color, highest thermal conductivity and excellent dispersion stability. Such results suggest that the direct adsorption of GO-based nanoparticles to support solar energy conversion may have various promising applications such as clean water production where there is abundant solar energy potential.